The Added Value of Whole-Exome Sequencing for Anomalous Fetuses With Detailed Prenatal Ultrasound and Postnatal Phenotype - He, Miao; Du, Liu; Xie, Hongning; Zhang, Lihe; Gu, Yujun; Lei, Ting; Zheng, Ju; Chen, Dan (Frontiers in Genetics, 2021)
Objectives To explore the added value of whole-exome sequencing (WES) in abnormal fetuses with detailed prenatal ultrasound and postnatal phenotype with normal karyotype and chromosomal microarray analysis (CMA). Methods Parents of fetuses with structural abnormalities by prenatal ultrasound who consented to provide fetal samples were prospectively recruited from January 2017 to December 2019. With aneuploidies or cases with copy number variations (CNVs) excluded, WES was performed for cases with normal karyotype and CMA results. Detailed prenatal ultrasound and postnatal imaging or pathology features were recommended for further interpretation of genetic variants. Results WES was performed for 94 eligible fetuses, DNA samples of which were extracted from 53 parent-fetus trios and 41 proband-only fetal tissues. A diagnostic genetic variant was identified in 37 (39.4%) of 94 fetuses, and 34 (64.2%) were detected in 53 trios, which was significantly greater than 3 (7.3%) in 41 proband-only cases (P<0.001). In 34 trios with diagnostic genetic variants, 23 (67.6%) were de novo and 11 (32.4%) were inherited with two homozygous and nine heterozygous variants. 14 (14.9%) of 94 fetuses had a variant of uncertain significance (VUS). Among 94 cases, six affected pregnancies continued and 88 terminated, and 57 of 88 terminated cases underwent postmortem examinations. With accurate phenotypes demonstrated by prenatal ultrasound and postnatal autopsies, the clinical phenotypes were correlated in 33 (89.2%) of 37 cases with specific genotypes, with the highest matching ratio in skeletal diseases (20/33, 60.6%). Conclusion WES has added value in the genetic diagnosis of abnormal fetuses with normal karyotypes and CMA, particularly in skeletal diseases. Using WES in various anomalous fetuses can broaden the understanding of prenatal phenotypes and genetic variants.